Improving market (cull) dairy cows' carcass traits and meat quality - N. Berdusco; D. Kelton; D. Haley; K.M. Wood; T.F. Duffield (Journal of Dairy Science)
ABSTRACT: Despite a high volume of market (cull) dairy cows entering the food chain every year, beef from market dairy cows is largely considered insignificant when compared with beef from beef cattle in the market and is widely thought to be usable for ground beef only. Our study aimed to evaluate the effects of feeding dairy market cows on a lactating TMR diet before slaughter on carcass and beef quality traits. Forty-three Holstein market cows were randomly assigned into 2 treatments: fed or direct. Fed cows (n = 22) were dried off and then fed a lactating cow TMR ration for approximately 60 d, whereas direct cows (n = 21) were sent directly to slaughter. Hot carcass weight (HCW) was used to calculate the dressing percentage (DP), together with the animals' BW, recorded when animals left the farm to go to the abattoir. At 24 h postmortem, the rib fat thickness (RFT) and rib eye area (REA) were measured by a certified grader. Afterward, rib samples were collected between the twelfth and tenth ribs from one side of the carcass and divided into 5 rib eye steaks. The first steak was used for intramuscular fat (IMF) content analysis by near-infrared spectroscopy. The other 4 steaks were then aged for 7, 14, 21, or 28 d. Following aging, the steaks available were assessed for tenderness using the Warner-Bratzler shear force protocol. Data were analyzed by mixed linear regression to compare experimental groups for continuous outcomes. The HCW of the fed cows was higher than the direct cows, with mean HCW of 408.3 kg and 326.1 kg, respectively (SE ± 9.0). Average DP in fed cows was 49.1%, compared with 42.5% in direct cows (SE ± 0.69). The average percentage of IMF in fed cows was 8.1% and 5.0% in direct cows (SE ± 0.43). Fed cows had a mean REA of 68.1 cm2, and direct cows had a mean of 57.7 cm2 (SE ± 11.9). No differences were found for RFT. The steaks aged for 14 d resulted in meat with a mean shear force (SF) of 4.19 kg in fed cows, whereas direct cows had a mean SF of 6.28 kg (SE ± 0.29). Feeding market dairy cows for 60 d before slaughter enhanced carcass weight and yield, IMF content, and tenderness. These results indicate that approximately 60 d of feeding can improve the quality of market dairy cow meat and may help improve market cow value.